The Event of Style in Literature - Aquilina, M. author. aut Link
XV, 249 p.
Keywords: The Event of Style in Literature brings discussions about the question of style up-to-date by schematising the principal issues relating to the topic through a critical overview of the canon of style studies. It reads the work of Jacques Derrida, Maurice Blanchot, and Hans-Georg Gadamer as groundbreaking and 'eventful' interventions.